2014
DOI: 10.1089/fpd.2013.1721
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Subtyping and Antimicrobial Susceptibilities ofCampylobacter coliIsolates from Diarrheal Patients and Food-Producing Animals in China

Abstract: The aim of this study was to determine the molecular subtyping and antimicrobial susceptibility characteristics of Campylobacter coli isolates from different sources in China. One hundred thirteen C. coli isolates were subtyped by pulsed-field gel electrophoresis (PFGE), multilocus sequence typing (MLST), and porA and flaA short variable region (SVR) nucleotide sequences. Cluster analysis was performed based on the PFGE and sequence types (ST). Eighty-four PFGE patterns (SmaI) were observed in 113 isolates. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 39 publications
2
20
2
1
Order By: Relevance
“…Because of the lack of large enough data to be representative of the diversity of C. jejuni in China, more studies need to be carried out to determine such differences. Most C. coli isolates belonged to ST-828 complex in our study, which correlated well with other studies in China, 39 South Korea, 37 America, 40 Portugal 41 and the Mediterranean area. 42 Surveillance programs monitoring antimicrobial resistance of Campylobacter and other foodborne pathogens have been established in several countries.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Because of the lack of large enough data to be representative of the diversity of C. jejuni in China, more studies need to be carried out to determine such differences. Most C. coli isolates belonged to ST-828 complex in our study, which correlated well with other studies in China, 39 South Korea, 37 America, 40 Portugal 41 and the Mediterranean area. 42 Surveillance programs monitoring antimicrobial resistance of Campylobacter and other foodborne pathogens have been established in several countries.…”
Section: Discussionsupporting
confidence: 92%
“…25 In addition, GEN, CLI and CHL are also used for antibiotic therapy. Antimicrobial resistance rates were also high in C. coli (73.3%, 63.3% and 20%, respectively), which was similar with the results of another study in north China 39 and Korea, 38 suggesting the emergence of resistance to these antimicrobials. Therefore, establishment of integrated surveillance networks in China and other countries should be taken into consideration.…”
Section: Discussionsupporting
confidence: 88%
“…The existence of high genotypic similarity amongst some strains isolated in Brazil is in contrast with previous studies conducted in several countries that showed high genomic diversity amongst C. coli strains (Harrington et al, 1997;Magnú sson et al, 2011;Giacomelli et al, 2012;Zhang et al, 2014). …”
Section: Discussioncontrasting
confidence: 96%
“…In recent years, frequent occurrences of aminoglycoside resistant Campylobacter isolates of animal and human origin have been reported in several countries (Guevremont et al, 2006;Pezzotti et al, 2003;Qin et al, 2011;Torralbo et al, 2015;Zhang et al, 2014), and in some studies, higher rates of streptomycin (STR) resistance have been detected in C. coli compared to C. jejuni (Giacomelli et al, 2014;Torralbo et al, 2015). Several mechanisms of aminoglycoside resistance have been described in Gram-positive and Gram-negative bacteria with the most important ones being alterations at the ribosomal binding sites (Carter et al, 2000;Meier et al, 1996;Olkkola et al, 2010;Torii et al, 2003) and enzymatic drug modification (for review see Ramirez & Tolmasky, 2010).…”
Section: Introductionmentioning
confidence: 99%